IMPLEMENTASI PROGRAM LITERASI AL-QUR’AN MELALUI METODE TILAWATI DALAM PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’AN DI SDIT AL-MUBAROK - Nurhazizah Nurhazizah; Instinganatul Ngulwiyah; Firdaus Firdaus (Jurnal Pendidikan Sultan Agung, 2026)
The ability to read the Qur'an is a crucial basic skill for students, yet many primary school students still struggle to read correctly according to tajwid rules. Therefore, an effective teaching method, such as the Tilawati method, is needed. This research is motivated by the importance of Qur'anic literacy in improving students' ability to read the Qur'an properly and correctly. The research questions include: (1) how is the Qur'anic literacy program using the Tilawati method implemented at SDIT Al-Mubarok, (2) what challenges and obstacles are faced during its implementation, and (3) what is the outcome or result of the Qur'anic literacy program with the Tilawati method on students. This study aims to describe the program's implementation, analyze the inhibiting factors, and evaluate the students' learning achievements. The research uses a qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that the Qur'anic literacy program with the Tilawati method is routinely conducted on Mondays, Tuesdays, and Thursdays through habituation and learning using Tilawati books and school teaching aids. The obstacles encountered include internal factors such as student discipline and motivation, and external factors such as parental support, the role of teachers, and the learning environment. The achieved output is the students' ability to recognize hijaiyah letters according to their makhraj and to understand basic Qur'anic recitations with tajwid.